THU0453 Efficacy of ab initio or very early introduction of immunosuppressive therapy in giant cell arteritis: a multicenter retrospective observational study. (12th June 2018) - Quartuccio, L.; Cavallaro, E.; Angelotti, F.; Capecchi, R.; Vitiello, G.; Cammelli, D.; Tavoni, A.; De Vita, S.
Abstract : Background: Glucocorticoids (GC) remain the mainstay of treatment of giant cell arteritis (GCA). However, relapses occur in up to 50% of patients when GC are tapered and prolonged courses of GC are associated with serious side effects. In this setting, the outcome is frequently determined by GC-related adverse events (AEs). Thus, several studies have been conducted on the effectiveness of a GC-sparing immunosuppressive therapy (IT), with conflicting results. Objectives: To evaluate the effectiveness of IT in a series of GCA patients, in: 1) reducing the risk of GCA relapse; 2) lowering the exposure to GC therapy; 3) minimising the occurrence of steroid-induced AEs. Methods: We performed a multicenter retrospective observational study including 69 patients (75, 4% females; mean age ±SD 68, 7±7, 8 y; median follow-up time 40 months [range 26–65]) diagnosed with GCA, all receiving an adjunctive IT given ab initio (71%) or within 3 months from the start of GC. All but 17 patients (with extracranic involvement) fulfilled the GCA ACR classification criteria. Risk of first relapse of GCA, GC exposure and main AEs were retrospectively analysed. Results were compared with those reported in other studies, all characterised by a lower use of IT. Results: all patients received GC plus IT: methotrexate up to 20 mg/week in 63 patients, cyclophosphamide in 22, tocilizumab in 12. In the follow-up, a first relapse of GCA occurred in 14 (20, 3%) of patients. The rates of first relapse at 12, 24, 36 and 48 weeks were 4, 3%, 11, 6%, 15, 9% and 15, 9%, respectively, in comparison with rates of 24, 3%, 41, 6%, 61%, 64, 9%, respectively, in the GC monotherapy arm in the meta-analysis by Mahr, 1 where similar data were available. The median daily prednisone dose at beginning was 50 mg, and decreased to 10 mg at 3 months and to 5 mg at 6 months. The median time required to reduce prednisone to 7.5 mg/day and 5 mg/ was 3 and 5 months respectively (vs. 6.5 and 7.5 months in series by Proven, 2 where similar data were available). In our cohort, lower cumulative GC use was accompanied by a reduction of AEs, without further toxicity (tab.1). Conclusions: The use of IT ab initio or very early in the treatment of GCA appears to be effective and safe, lowering the risk of relapses, reducing GC dose and the rate of GC-related AEs. Therefore, the present data support the early introduction of IT in the treatment of GCA. References: [1] Mahr AD, et al. Arthritis Rheum2007;56(8):2789–97. [2] Proven A, et al. Arthritis Rheum 2003 49(5):703–8.[3] Souza AW, Okamoto KY, Abrantes F, et al. Clinics (Sao Paulo) 2013;68:317–322.[4] Alba MA, et al. Medicine (Baltimore) 2014;93( 5 :194–201.[5] Labarca C, et al. Rheumatology (Oxford) 2016;55( 2 :347–56.Disclosure of Interest: None declared